KOMODIFIKASI KESENIAN TRADISIONAL WACANA ESTETIKA POSMODERN DALAM PARIWISATA - Kasman, Selvi (Institut Seni Indonesia Padang Panjang, 2011)
Traditional ArtÂ as one of tourism sector object especially cultural tourism experience of transformation bearing various artistic form of culture popular. Tourism capitalism, making traditional artbecome art show of which have experienced of arts is pseudotradisonal komodification. Where happened ( solidarity akulturasi) between its creator folk art value with audience appetite, and reckon economic value because art possible represent product of social which is isstrongest to be attributed to economic bases, economic part, action economic Â and economic production. That artistry relate at traditional from, but its value, its and symbolism of artthe taken off, hence term with art of tourist which is special it is true for the consumption of tourist.